ENHANCING GOVERNMENT INTERNAL AUDITOR PERFORMANCE THROUGH COMPETENCE AND GOAL ORIENTATION - Herra Gusrifan; Vince Ratnawati; Ria Nelly Sari (CURRENT: Jurnal Kajian Akuntansi dan Bisnis Terkini, 2026)
The role of internal auditors is crucial as an early warning system for violations or irregularities that indicate corruption, collusion, and nepotism, both in central and regional governments. Government internal auditors are expected to detect fraud early on that could harm state finances. However, in reality, the practice of corruption, collusion, and nepotism continues and is increasing. This raises questions about the effectiveness of government internal auditors. This study aims to examine and analyze the influence of competence and goal orientation on auditor performance. The study population consisted of auditors in Inspectorates throughout Riau Province, with 214 auditors selected through purposive sampling. The analytical method used in this study is Structural Equation Modeling (SEM). The novelty of this study is the incorporation of motivational goal orientation that psychologically actualizes auditors' technical capabilities, resulting in reliable performance improvements in high-risk environments. Public sector oversight needs to shift the focus of its capacity-building initiatives from merely developing technical skills to fostering a flexible and learning-oriented attitude.